2015
DOI: 10.1002/ijc.29712
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the integration of human papillomaviruses in head and neck tumours in relation to patients' prognosis

Abstract: Integration, which leads to the disruption of the circular HPV genome, is considered as a critical, albeit not obligatory, step in carcinogenic progression. Although cervical carcinomas with extrachromosomal HPV plasmid genomes have been described, the virus is integrated in 70% of HPV16-positive cervical tumours. Limited information is available about HPV integration in head and neck tumours (HNC). In this study, we have characterised the physical status of HPV in a set of tonsillar tumour samples using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 44 publications
2
54
2
Order By: Relevance
“…The fact that the episomal and integrated HPV can co-exist in the same tissue or even the same cell (30, 32, 47, 48), and both can be transcribed, adds another twist to the complex picture of HPV infection in human cancers. Southern blots or FISH-based technologies followed by high-resolution microscopy might help to resolve this scientific dispute (32, 49), and should be evaluated in conjunction with H3K27ac binding sites in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the episomal and integrated HPV can co-exist in the same tissue or even the same cell (30, 32, 47, 48), and both can be transcribed, adds another twist to the complex picture of HPV infection in human cancers. Southern blots or FISH-based technologies followed by high-resolution microscopy might help to resolve this scientific dispute (32, 49), and should be evaluated in conjunction with H3K27ac binding sites in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of HPV-integration is controversial, recent studies have demonstrated that HPV+ HNSCC samples with episomal and integrated HPV have unique signatures of gene expression, and can be separated based on them (22, 30, 32, 4749). Clustering of gene expression data described two HPV+ HNSCC subtypes: mesenchymal and classical (29).…”
Section: Discussionmentioning
confidence: 99%
“…Neither the physical status of HPV DNA (integrated vs. episomal) nor the transcriptional activity of E6/E7 oncogenes was examined. Vojtechova et al reported that both integrated and episomal HPV was associated with a significantly better prognosis compared with HPV− cases of OPSCC [38]. HPV DNA alone is not sufficient to claim causality in LSCC.…”
Section: Tong Et Al: Prognostic Significance Of Hpc In Laryngeal Cancermentioning
confidence: 99%
“…Transcription of the X gene was observed in two out of eight (25.00%) cell lines analyzed, but none expressed the S gene [46]. Nine out of nine (100%) HPV integrants were expressing E6 mRNAs but only seven (77.78%) were also transcribing for messenger RNAs bearing E7 [52]. Other studies reported integrants active only in certain tissues: in transgenic C57BL/6 mice, HBV particles or HBsAg were expressed in various amounts and in distinct sites in different subjects [53,54].…”
Section: Resultsmentioning
confidence: 98%
“…For instance, the amplification of papillomavirus oncogene transcripts (APOT) assay specifically amplifies viral messengers from transcriptionally active integrants but cannot detect the integrants directly [52], therefore silent integrants are missed. On the other end, detection of integrated papillomavirus sequences (DIPS) is used to characterize the sequence structure of the viral integrants, particularly at the virus-cell junctions, but it is not designed to query the transcriptional activity [75], thus it cannot assess the expression status of the proviruses.…”
Section: 2217/fvl-2017-0063mentioning
confidence: 99%